Investigating the Role of Accounting Information in Investment Decisions and Supply Chain Management - Talib, Ali Bayan; Lafta, Oday Takleef (International Journal of Supply Chain Management, 2019)
Today, competition between organizations and companies has become a global competition. Because of the creation and expansion of this global competition among different businesses and companies, many organizations are looking for ways to gain competitive advantage. One of the ways to gain competitive advantage is to focus on the supply chain and improve it. By providing timely, accurate and credible information, information technology improves the performance of the company and its partners in the supply chain. The use of IT tools has affected the supply chain capabilities and subsequently, the supply chain performance is also affected. For this reason, this study examines the impact of information technology on supply chain management. Based on the results of the research, it was determined that the use of information technology in supply chain management increases the quality, reliability and accuracy of information, operational efficiency and improving performance, coherence and collaboration, reducing costs and differentiating products or services.